The relationship between knowledge and adolescents' attitudes towards early marriage - Pusporini, Lenny Stia; Alifiani, Herna; Siska (Utan Kayu Publishing, 2024)
Early marriage has emerged as a critical issue in societal development, especially among adolescents, attracting attention at both international and national levels. With the prevalence of early marriage reaching up to 41.9% in some countries, including Indonesia, this issue demands special attention to mitigate its negative impacts on education, health, and social welfare of adolescents. This study aims to analyze the relationship between adolescents' knowledge and their attitudes towards early marriage in Sindang Heula Village, Serang Regency, in 2023, focusing on how specific knowledge about the consequences of early marriage influences adolescents' attitudes. The research methodology employs a cross-sectional design, selected to evaluate the influence of knowledge on adolescents' attitudes towards early marriage at a specific point in time, involving a total sample of 91 respondents from the adolescent population in Sindang Heula Village, which totals 1,090 individuals. Univariate analysis results show that 55.0% of adolescents have insufficient knowledge about early marriage, and an equal number exhibit negative attitudes towards early marriage. Bivariate analysis reveals a significant relationship between knowledge and adolescents' attitudes towards early marriage. Based on these findings, this study recommends that stakeholders, especially health professionals, regularly conduct socialization or education about early marriage to ensure that the community, particularly adolescents, understand the impact of early marriage, thereby encouraging a decrease in early marriage rates.